2018
DOI: 10.1177/1071100718781096
|View full text |Cite|
|
Sign up to set email alerts
|

Fixation Techniques: Proceedings of the International Consensus Meeting on Cartilage Repair of the Ankle

Abstract: This international consensus derived from leaders in the field will assist clinicians with using fixation techniques in the treatment of osteochondral lesions of the talus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
(20 reference statements)
1
30
0
Order By: Relevance
“…Fixation of the osteochondral fragment was indicated for large lesions with intact or nearly normal articular cartilage. 27 This procedure was performed in 28 ankles (27 patients) using the PLLA pin between January 2004 and December 2018 at our hospital. Among them, 7 ankles were excluded because no tissue was obtained intraoperatively from the osteochondral fragment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fixation of the osteochondral fragment was indicated for large lesions with intact or nearly normal articular cartilage. 27 This procedure was performed in 28 ankles (27 patients) using the PLLA pin between January 2004 and December 2018 at our hospital. Among them, 7 ankles were excluded because no tissue was obtained intraoperatively from the osteochondral fragment.…”
Section: Methodsmentioning
confidence: 99%
“…5 Osteochondral fragments should be fixed when the fragment is relatively large, at least 3 mm in thickness and 10 mm in diameter, with a nearly normal articular cartilage surface. 27 Several fixation procedures are available for treating OLT, including cortical bone pegs, 17 biocompression screws, 14 and bioabsorbable pins. 15,21,22 Bioabsorbable bone fixation is advantageous because there is less interference from the articular cartilage because of the small diameter of the device, and it is unnecessary to harvest healthy tissue and remove the implant.…”
mentioning
confidence: 99%
“…The advantage of this technique is the restoration of the natural congruency of the joint and the preservation of the hyaline cartilage in the lesion. 29 Several studies have reported good clinical results using this treatment. 8,12,27,31 Generally, indications for the fixation technique include an intact osteochondral fragment larger than 10 mm in diameter with a bony portion of at least 3 mm in thickness.…”
mentioning
confidence: 92%
“…8,12,27,31 Generally, indications for the fixation technique include an intact osteochondral fragment larger than 10 mm in diameter with a bony portion of at least 3 mm in thickness. 29 However, bone in the fragment has various morphologies, especially the subchondral bone plate. 21 Some cases show disruption of the subchondral bone plate or the appearance of a normal subchondral bone plate in the osteochondral fragment.…”
mentioning
confidence: 99%
“…8,9,19 However, it is recommended for small lesions of <107.4 mm 2 in area and/or 10.2 mm in diameter. 25,26 For large lesions, replacement surgery such as autologous osteochondral transplantation or osteochondral allografting is required. 1,16,19,23,27 Despite their excellent clinical results, these replacement procedures are not without risks or complications.…”
mentioning
confidence: 99%